Towards sustainable socio-economic development in improving livelihoods - Mkhatshwa-Ngwenya, E. N. M.; Khumalo, P. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
This paper critiques sustainable socio-economic issues which strive to improve livelihoods. Based on literature review, it argues for the use of local resource-based approaches, partnership, and effective participation of stakeholders. The local resource-based approach and technologies are cost-economic, distinctive and advance socio-economic growth that will sustain itself. Consequently, the paper reviews a few other countries in Africa where local resource-based approaches are a success. The paper further seeks to argue that the success of local resource-based approach in improving livelihoods towards sustainable socio-economic growth is undermined by lack of partnership policy, and minimal innovative programmes and projects. Through literature review, the sustainable socio-economic growth contribution of enterprise development, innovative public employment programmes (IPEPs) by way of skills transfer and training, creation of opportunities to earn a living, social cohesion, and quality infrastructure development is analysed. Successively, there is a discussion on the challenges faced by Governance in improving socio-economic growth. These are the inequality, discriminatory laws, policies and practices, and lack of visionary committed and accountable leadership to job creation to underpin all aspects of policymaking. As a result, the equilibrium on the inequality to fast track the socio-economic transformation is enhanced. This paper is descriptive in nature utilises human capital development approach as the theoretical lenses employs to address the challenges of unemployment, poverty so as to achieve sustainable growth and development. To arrive to its objective, the paper elucidates some of the possible solutions to assuage this challenge, among which are the need for innovative approaches such as an enabling environment for enterprise development, enforcing partnership equity policy, and inclusion of skills training in the education curriculum. Moreover, the overall value of innovative PEPs as an employment intervention strategy stimulate confidence and rekindle dignity to the participants and their family members. Consequently, transformational benefits are expected to be achieved. The paper accentuates the need for further research on the evaluation mechanism that will monitor the effectiveness of enterprise development and entrepreneurship using local labour-based resource approaches in improving livelihoods.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Economic-development; Job creation; Local-development; Livelihoods; Poverty; Economic development -- South Africa; Local government -- South Africa